The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.37201/req/122.2022
|View full text |Cite
|
Sign up to set email alerts
|

Insights for COVID-19 in 2023

Abstract: Predictions for a near end of the pandemic by the World Health Organization should be interpreted with caution. Current evidence indicates that the efficacy of a fourth dose of classical mRNA vaccines (BT162b2 or mRNA-1273) is low and short-lived in preventing SARS-CoV-2 infection in its predominant variant (Omicron). However, its efficacy is high against severe symptomatic infection, hospitalization and death. The new vaccines being introduced are bivalent and active against the Omicron variants. Potential ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 86 publications
(117 reference statements)
0
32
0
Order By: Relevance
“…Increasing overall vaccine coverage is greatly needed, particularly as new variants continue to emerge. 9 , 10 There is an urgent need to increase coverage in children specifically, given the protective benefits and the broader epidemiologic dividend of vaccinating children. 11 Unfortunately, in a recent survey of 1847 US adults, only 62% thought COVID-19 vaccines were safe for children ages 12 to 17, 55% thought they were safe for children ages 5 to 11, and 48% thought they were safe in very young children (0-4).…”
Section: Purposementioning
confidence: 99%
“…Increasing overall vaccine coverage is greatly needed, particularly as new variants continue to emerge. 9 , 10 There is an urgent need to increase coverage in children specifically, given the protective benefits and the broader epidemiologic dividend of vaccinating children. 11 Unfortunately, in a recent survey of 1847 US adults, only 62% thought COVID-19 vaccines were safe for children ages 12 to 17, 55% thought they were safe for children ages 5 to 11, and 48% thought they were safe in very young children (0-4).…”
Section: Purposementioning
confidence: 99%
“…Previously, several articles have been published on the impact of COVID-19 on environmental factors, where multiple study showed a significant correlation between climatic indicators like humidity, temperature, due point, wind speed rainfall and SARS-CoV-2 induced fatality. 27. , 28.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] However, the ongoing risks posed by emergence of newer and rapidly evolving variants of SARS-CoV-2 (Alpha, Beta, Gamma, Delta, Epsilon, Omicron to name a few) have raised concerns against the management practices and demand timely research to combat the situation. [23][24][25][26][27][28] Therefore, the significance of this review lies in unraveling the intricate interplay between SARS-CoV-2 and cancer and present an arena of scientific inquiry holding potential ramifications for clinical practice and therapeutic strategies. By synthesizing the available knowledge, the objectives of this review are to provide a comprehensive understanding of the challenges and opportunities that have arisen at the juncture of COVID-19 and cancer, ultimately guiding future research directions and shaping the evolution of cancer care in a postpandemic landscape.…”
Section: Introductionmentioning
confidence: 99%